Circulating Vitamin D Concentrations and Risk of Atrial Fibrillation: A Mendelian Randomization Study Using Non-deficient Range Summary Statistics - Zhang, Nan; Wang, Yueying; Chen, Ziliang; Liu, Daiqi; Tse, Gary; Korantzopoulos, Panagiotis; Letsas, Konstantinos P.; Goudis, Christos A.; Lip, Gregory Y. H.; Li, Guangping; Zhang, Zhiwei; Liu, Tong (Frontiers in Nutrition, 2022)
Background and aims: Vitamin D deficiency is a common disorder and has been linked with atrial fibrillation (AF) in several observational studies, although the causal relationships remain unclear. We conducted a Mendelian randomization (MR) analysis to determine the causal association between serum 25-hydroxyvitamin D [25(OH)D] concentrations and AF. Methods and results: The analyses were performed using summary statistics obtained for single-nucleotide polymorphisms (SNPs) identified from large genome-wide association meta-analyses conducted on serum 25(OH)D (N=79,366) and AF (N=1,030,836). Six SNPs related to serum 25(OH)D were used as instrumental variables. The association between 25(OH)D and AF was estimated using both the fixed-effect and random-effects inverse variance weighted (IVW) method. The MR analyses found no evidence to support a causal association between circulating 25(OH)D level and risk of AF using random-effects IVW (odds ratio per unit increase in log 25(OH)D = 1.003, 95% CI, 0.841-1.196; P = 0.976) or fixed-effect IVW method (OR=1.003, 95% CI, 0.876-1.148; P = 0.968). Sensitivity analyses yielded similar results. No heterogeneity and directional pleiotropy were detected. Conclusion: Using summary statistics, this MR study suggests that genetically predicted circulating vitamin D concentrations, especially for a non-deficient range, were not causally associated with AF in the general population. Future studies using non-linear design and focusing on the vitamin D deficiency population are needed to further evaluate the causal effect of vitamin D concentrations on AF.